A note on properties of hypermetric spaces - M. Alimohammady; S. Jafari; S. Moshokoa; M. Koozehgar Kalleji (Journal of Hyperstructures, 2014)
The note studies further properties and results of analysis in the setting of hypermetric spaces. Among others, we present some results concerning the hyper uniform limit of a sequence of continuous functions, the hypermetric identification theorem and the metrization problem for hypermetric space.